Peranan Pembelajaran Sejarah Sebagai Upaya Membentuk Karakter Peserta Didik Pada Kurikulum Merdeka - Aldi Cahya; Tarunasena (Visi Sosial Humaniora, 2024)
This research is based on the idea that character education is a way to overcome the problems of the current multidimensional crisis. Qualitative approach with literature study, is used in this research because this type of study requires theoretical analysis and some scientific literature references. The data used in this research comes from relevant literature, such as books, journals, or scientific articles on the chosen topic. The result of this research discussion is that the Independent Curriculum, launched by the Indonesian Ministry of Education and Culture, regulates character education including in the realm of history learning. The Independent Curriculum emphasizes learning that is more flexible, inclusive, and learner-centered with the aim of creating learners who are independent, creative, and have character. History education is very important for building character, Indonesian civilization because through history students can recognize the identity of their nation.